Patrones y tendencias de uso del venado cola blanca (Odocoileus virginianus) en comunidades mayas, Campeche, México - Retana Guascón, Oscar Gustavo; Martínez-Pech, Lucia Guadalupe; Niño-Gómez, Graciela; Victoria-Chan, Eloy; Cruz-Mass, Ángeles; Uc-Piña, Alejandro (THERYA, 2015)
Introduction: For some indigenous societies of Mexico, white-tailed deer (Odocoileus virginianus) has played and still plays a decisive role in terms of its cultural and practical significance. In this sense, the objective of this study was to obtain information concerning the diverse ways that Mayan populations of Campeche State using the white-tailed deer with the aim of detecting patterns and trends of use on this species. Methods: Fieldwork (2009-2012) was carried out in four rural communities, Nunkiní and Sahcabchén located in the northern portion of Campeche, and Pich and Chencoh located in the central part of the state. Interviews (n = 160) were performed to record the uses and values people assign to the wildlife in each community. Using the relative importance index (IIRE) and the similarity index (IS), a comparison was made between communities regarding white-tailed deer values and uses. Results: In the four Mayan communities, uses of white-tailed deer (O. virgininianus) can be classified in eight categories: 1) food, 2) medical, 3) furrier, 4) tool, 5) ornamental, 6) trade, 7) pets, and 8) mythical. The use of deer as food showed an IS > 0.8 in four communities. Skin trade was recorded differently with Pitch having a higher value of importance with respect to the communities of Chencoh, Sahacabchen and Nunkiní, where IS held in a range from 0.4 to 0.6. The most significant differences were obtained for skin trade showing a similar index between Sahacabchen and Nunkini (IS > 0.6 ) while lacking commercial value in Chencoh and Pich (IS < 0.1). Discussion and conclusions: The recognized patterns of use of white-tailed deer recognized are related to the historical characteristics of utilization and management of natural resources of the Mayan communities, where agriculture is the predominant economical activity and hunting is an opportunistic and occasional practice for subsistence. This pattern of use has remained relatively stable and the practices and categories of use are similar among Mayan populations despite the distance between them ( 100 km). However, communities in Northern Campeche (Nunkiní and Sahcabchen) showed a growing tendency to trade the skin with respect to communities of Central Campeche (Chencóh and Pich) where the traditional pattern of use remained essentially for food, ornamental and household use of skin, with a tendency towards implementing hunting in legally established wildlife management units (UMA).